The Logic of Pro-Poor Policymaking: Political Entrepreneurship and Mass Education. Issue 2 (23rd January 2013) - Kosack, Stephen
<x content-type="archive" xml:space="preserve">Abstract</x> This article argues against the scholarly consensus that governments make pro-poor policies when they are democratic. In democracies and autocracies, a government's strongest incentive is to serve citizens who are organized, and poor citizens face collective-action disadvantages. But a 'political entrepreneur' can help poor citizens organize and attain power with their support; to stay in power, the political entrepreneur's incentive is to maintain poor citizens' support with pro-poor policies. Politics and education are analyzed over half-a-century in countries with little in common – Ghana, Taiwan, and Brazil. Governments that expanded education for the poor were more often autocratic than democratic, but were always clearly associated with political entrepreneurs. The results suggest an alternative understanding of government incentives to serve poor citizens.